How to translate rock: genealogy and validity of rock versions in Spanish (Anclajes, 2026)
Since the appearance of rock in Spanish-speaking societies, the translation ofsongs has been transcendental in the dissemination of the genre. To verify this relevance and investigate its validity for more than five decades, a corpus of 38 foreign songs and their corresponding versions in Spanish from 1960 to the present was analyzed. As a result of this study, the procedures used to develop these songs were identified, reducing the methods applied by the musicians to three possibilities: calque, gloss or free version,depending on the degree of imitation of the original song.
Keywords: Popular Music; Rock; Song; Translation; Spanish Culture